The protective effects of omega-3 fatty acids against MK-801-induced neurotoxicity in prefrontal cortex of rat - Ozyurt, Birsen; Sarsilmaz, Mustafa; Akpolat, Nusret; Ozyurt, Huseyin; Akyol, Omer; Herken, Hasan; Kus, Ilter (Pergamon-Elsevier Science Ltd, 2007)
The aims of this study are to investigate the contribution effect of oxidative stress in MK-801-induced experimental psychosis model, and to show that prevention of oxidative stress may improve prognosis. Because oxidative damage has been suggested in the neuropathophysiology of schizophrenia, the possible protecting agents against lipid peroxidation are potential target for the studies in this field. For this purpose, Wistar Albino rats were divided into three groups: the first group was used as control, MK-801 was given to the rats in the second group and MK-801 + omega - 3 essential fatty acids (EFA) was given to the third group. MK-801 was given intraperitoneally at the dose of 0.5 mg/(kg day) once a day for 5 days in experimental psychosis group. In the second group, 0.8 g/(kg day), omega - 3 FA (eicosapentaenoic acid, 18%, docosahexaenoic acid, 12%) was given to the rats while exposed MK-801. In control group, saline was given intraperitoneally at the same time. After 7 days, rats were killed by decapitation. Prefrontal brain area was removed for histological and biochemical analyses. As a result, malondialdehyde (MDA), as an indicator of lipid peroxidation, protein carbonyl (PC), as an indicator of protein oxidation, nitric oxide (NO) levels and superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) activities as antioxidant enzymes, and xanthine oxidase (XO) and adenosine deaminase (AD) activities as an indicator of DNA oxidation was found to be increased significantly in prefrontal cortex (PFC) of MK-801 group (P < 0.0001) compared to control group. In omega - 3 FA treated rats, prefrontal tissue MDA, PC and NO levels as well as SOD, GSH-Px, XO, and AD enzyme activities were significantly decreased when compared to MK-801 groups (P < 0.0001) whereas catalase (CAT) enzyme activity was not changed. Moreover, in the light of microscopic examination of MK-801 groups, a great number of apoptotic cells were observed. w - 3 FA supplementation decreased the apoptotic cell count in PFC. The results of this study revealed that oxidative stress and apoptotic changes in PFC may play an important role in the pathogenesis of MK-801-induced neuronal toxicity. This experimental study also provides some evidences for the protective effects of omega - 3 FA on MK-801-induced changes in PFC of rats. (c) 2006 Published by Elsevier Ltd.
Keywords: apoptosis; malondialdehyde; MK-801; omega-3 fatty acids; prefrontal cortex; protein carbonyl; oxidative stress